Hierarchically porous calcium-based composites synthesized by eggshell membrane templating for thermochemical energy storage of concentrated solar power. (1st August 2022) - Huang, Caifeng; Xu, Min; Huai, Xiulan; Liu, Zhangli
Abstract: Thermochemical energy storage (TCES) based on the calcium-looping (CaL) process is considered as a promising strategy to realize more-efficient concentrating solar power using a supercritical carbon dioxide cycle. However, developing high energy and power density, cycling stability and cost-effective calcium-based TCES materials is still a significant challenge due to their rapid deactivation induced by sintering. Herein, we report the high-performing Ca-based composites templated by eggshell membranes (ESM) using a facile sol-gel method for thermochemical energy storage. The hierarchically-ordered calcium-based materials are characterized by macroporous and mesoporous networks composed of MgO-stabilized CaO nanoparticles, which exhibit large surface area and abundant porosity enabled by highly porous interwoven fibrous structures of ESM template. The synthetic composites with 20 wt% MgO doping offers superior CO2 uptake, high carbonation rate and cycling stability during the 20 carbonation-calcination cycles. Importantly, the CaO/MgO pellets constructed by this morph-genetic material shows the TCES potential of achieving a high energy storage density of 2.58 GJ/m 3, extraordinary power density of 720 W/kg, and sufficient crushing strength. It is contributed by the rapid CO2 diffusion rate and high resistance to pore-plugging and collapse derived from the three-dimensional hierarchical structures of the as-obtained materials. The excellent performance makes the ESM-templated calcium-based materials promising alternative to realize high-efficient thermochemical energy storage for concentrated solar power. Highlights: CaO/MgO composites were synthesized using eggshell membrane as biotemplate. The composites possess hierarchical structure with superior CO2 uptake. The composites exhibit high energy and power density for thermochemical energy storage. Pore-plugging is reduced by the MgO dopping and microstructure of the composites.